Performance tests using the Lexsyg luminescence reader - Lomax, Johanna; Kreutzer, Sebastian; Fuchs, Markus (Geochronometria, 2014)
This study presents test measurements on a Lexsyg luminescence reader, acquired by the Giessen luminescence group. The reader is of the type Standard, hence designed for routine determination of palaeodoses using quartz or K-feldspars. The tests include measurements of the stimulation powers,...